2011
DOI: 10.1128/jvi.00661-11
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pancreatropic Coxsackievirus Vector Expressing Glucagon-Like Peptide 1 Reduces Hyperglycemia in Streptozotocin-Treated Mice

Abstract: A coxsackievirus vector, vCVB(dm) (v stands for vector, CVB stands for group B coxsackievirus, and dm stands for double mutant), has been produced from a unique strain of coxsackievirus B3 (CVB3) containing 2 mutations that confer the property of highly selective pancreatropism. This vector has been tested as a delivery vehicle for glucagon-like peptide 1 (GLP-1), a peptide that enhances pancreatic regeneration following tissue damage. vCVB(dm) is a live vector comprising the entire plus-strand RNA genome with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Our findings further indicated that insulin resistance, along with low-intensity and highintensity endurance activities in diabetic rats, decreased significantly. Similarly, the destruction of pancreas by STZ leads to a sharp decrease in insulin levels, and owing to hyperglycemia (20), the loss of muscle mass is observed in the models of a severe decrease in insulin (30). Frequent impulses during training are also shown to coordinate the enzymes associated with the metabolism of IMTG (31), because of which endurance-trained athletes have high amounts of IMTG but are insulin sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings further indicated that insulin resistance, along with low-intensity and highintensity endurance activities in diabetic rats, decreased significantly. Similarly, the destruction of pancreas by STZ leads to a sharp decrease in insulin levels, and owing to hyperglycemia (20), the loss of muscle mass is observed in the models of a severe decrease in insulin (30). Frequent impulses during training are also shown to coordinate the enzymes associated with the metabolism of IMTG (31), because of which endurance-trained athletes have high amounts of IMTG but are insulin sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of GLP-1-expressing vCVB(dm) (vCVB(dm)GLP-1) reduced STZ-induced hyperglycaemia in diabetic Balb/c mice through enhancement of pancreatic insulin content and stimulation of beta-cell neogenesis (Ref. 80). However, vCVB(dm)GLP-1 could provide only transient gene expression lasting 4–7 days due to low transduction rate, inflammatory response and inability to integrate into the host genome.…”
Section: Critical Evaluation Of Glp-1-mediated Gene Therapy Approachesmentioning
confidence: 99%
“…Therapeutic gene delivery systems with various gene carriers including nonviral vectors are potential solutions to the limitations of current diabetic treatments. Nonviral gene delivery is achieved by either nano-size gene complexation or adsorption of the gene to nanoparticles through an interaction between negatively charged DNA and nonviral cationic carriers such as polymers, lipids and inorganic materials [ 8 ]. Recent advances and consideration of the prospects for their application provide better methods of diabetic treatment, primarily for the prevention and cure of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances and consideration of the prospects for their application provide better methods of diabetic treatment, primarily for the prevention and cure of T2DM. However, direct intravenous injection of these systems limited further application of gene delivery regarding serum stability, immunogenicity, low transfection efficiency and high costs, encouraging researchers to focus on alternative systems [ 8 , 14 20 ].…”
Section: Introductionmentioning
confidence: 99%